The Impact of International Cooperation Programs and Scholarly Exchanges on the Cultivation of International Talent through Internationalization Development Strategy: Evidence from Universities in Heilongjiang Province, China (Architecture Image Studies, 2025)
This study investigates the mechanisms through which international cooperation programs (ICP) and international student exchange (ISE) contribute to the development of collaborative international ties (CIT), with international scholarly exchanges (IDS) examined as a mediating factor. Using structural equation modeling (SEM), data were analyzed to test seven hypotheses. The results show that while ICP did not significantly predict IDS, ISE had a strong positive effect on IDS, highlighting the importance of academic mobility in fostering scholarly collaboration. Both ICP and ISE directly enhanced CIT, and IDS further reinforced CIT, confirming its mediating role. Mediation analysis revealed that IDS did not mediate the relationship between ICP and CIT but significantly mediated the effect of ISE on CIT. These findings underscore the centrality of student exchanges and scholarly collaboration in building sustainable international partnerships. The study contributes to the literature on higher education internationalization by clarifying the pathways through which institutional strategies influence global academic ties and provides practical insights for policymakers and universities aiming to strengthen international collaboration.